Early educational trajectories of children with autism spectrum disorder in Chile: challenges and facilitators - Martinez, Camila; Davidoff, Alexandra; Briceño, Rocío (Frontiers in Education, 2023)
Inclusive education and special education are the means of education for people with special educational needs and specific disabilities. Inclusive education has been promoted in recent decades as the optimal method of educating in diversity. However, in Chile, access to quality education remains a major challenge for students and their families. In this article, we explore the experiences, motivations, and main factors in making early educational decisions by families and caregivers of children on the autism spectrum. In particular, using six semi-structured interviews conducted with families and caregivers of children, we study the process of initial entry into the educational system, including parents' perceptions and knowledge of the access routes to it and the facilitators and barriers present for their incorporation. The results indicate that, from the very beginning, the information available social and family attitudes, may hinder children's access to the available care and education system, with a generalized demand to strengthen social and institutional support networks. In general, and as may be expected, educational decisions, trajectories, and expectations are interdependent and evolve with the experience of caregivers and children in the educational system and their families.